Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantukan Media Cardboard dalam Meningkatkan Kemampuan Berpikir Kritis Siswa: The Application of the Teams Games Tournament (TGT) Cooperative Learning Model Assisted by Cardboard Media to Enhance Students Critical Thinking Skills - Septin, M. Dimas; Gumilar, Gugum; Gumilar, Rendra (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to improve students' critical thinking skills in economics by applying the Teams Games Tournament (TGT) cooperative learning model assisted by cardboard media. This research used a quasi-experimental method with a non-equivalent control group design and a quantitative approach. The population for this study was all 91 students of class XI IPS at SMA 1 Baregbeg. The researcher used a purposive sampling technique to select the sample, with class XI IPS 3 as the experimental group (31 students) and class XI IPS 2 as the control group (30 students). The test instrument used was a set of questions to measure students' critical thinking skills, which had been previously pilot-tested. The research findings indicate that there was a difference in the improvement of students' critical thinking skills before and after the treatment in both the experimental and control groups. This is demonstrated by the increase in the average pretest and posttest scores, from 50.11 to 87.85 in the experimental group, and from 65.44 to 77.89 in the control group. The results of this analysis show that the Teams Games Tournament (TGT) cooperative learning model assisted by cardboard media is more effective in enhancing students' critical thinking skills compared to conventional learning models.